Strategy and strategic choice: The case of telecommunications - Butler, Richard J.; Carney, Mick (Strategic Management Journal, 1986)
Abstract This paper outlines a model of organizational strategy that takes into account both the task ambiguity and concentration of the environment. A competitive strategy, in the sense as used in classical economics, is most suitable with low task ambiguity and concentration. When task ambiguity increases a shift to an innovative strategy can be expected. When concentration is high consolidative and cooperative strategies with respectively low and high ambiguity can be expected. These latter two strategies, in particular, tend to impose institutional and regulatory constraints upon firms, an aspect that is seriously neglected in the conventional business policy and strategic management literature. This model is illustrated using the case of the British telecommunications industry which has recently been subject to considerable regulatory and technical change. Implications for management are that strategy should be matched to environmental conditions as defined by task ambiguity and concentration. However, these dimensions are not fixed but enacted by firms in a particular industry. Implications for government are that a more contingent approach to regulation and de‐regulation needs to be considered.